Analisis Keterampilan Abad 21 Siswa dengan Pendekatan Culturally Responsive Teaching Terintegrasi Etnokimia - Runi Robo; Tamrin Taher (Peneliti.net, 2021)
This study aims to develop 21st century skills of students in hydrolysis material using a culturally responsive teaching approach which is integrated with ethnochemistry. This research was conducted in the even semester of the 2018/2019 academic year involving 19 students of class XI IPA Aliyah Alkhairaat Guraping. This study uses a qualitative method that focuses on the development of 21st century students' skills in salt hydrolysis material. The collected data is taken through reflective student journals, student interviews and observers' classroom observations. The standard quality in this study is trusthworthiness by using pre-engagement, persistent observation, progressive subjectivity, and member checking. Based on the results of the study of salt hydrolysis learning using a culturally responsive teaching approach it can be seen that 21st century students' skills, namely information skills, automation skills and communication skills are seen by the use of this approach. In addition, students' motivation and curiosity also develop. Culturally responsive teaching can be used as an alternative to develop 21st century skills for students in learning hydrolysis of salt.